language for health care (Dùng kèm sách số ĐKCB MON.045130) (New York, 2002)
This text teaches medical terminology by familiarizing students with how medical terms are formed and by providing a systematic learning structure. The first three chapters of the text introduce how medical terms are formed and the major word parts from which many of the terms are formed. Chapters 4 through 16 are the body systems chapters. The remaining chapters cover additional medical terminology.
Keywords: Medicine,Medical sciences,Khoa học y khoa,Y khoa